Oncogenesis, Inflammatory and Parasitic Tropical Diseases of the Lung - Kayembe, Jean-Marie (IntechOpen, 2013)
In this book dealing with the lung health, the authors focus on various fields, spreading from pulmonary oncogenesis, to inflammatory and parasitic lung diseases. The first section deals with the fundamental research on lung cancer that is mandatory for the development of novel and early biomarkers for diagnosis of the lung cancer. This development could be enhanced using experimental models despite the species barrier. Mouse models can help us understand the sequence of events involved in human lung neoplasia and their underlying molecular mechanisms. The results of the research could be used to identify novel targets for the development of new biological therapies. In the second section of this book, the role of inflammation in various respiratory diseases is outlined. The authors recall cellular mechanisms including neutrophils to improve the understanding of the phenomenon and help develop targeted therapies. The third section on parasitic tropical lung disease highlights the growing importance of neglected tropical diseases due to increased traffic across the continents and migration of the population. Physicians need to be aware of the symptoms and imaging findings of these diseases mainly in travelers and immigrants from tropical endemic areas.